Architectural Draughtsmanship From Analog to Digital Narratives - Castaño Perea, Enrique; Echeverria Valiente, Ernesto; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This is the proceedings of the XVI International Congress of Graphic Design in Architecture, EGA 2016, held in Alcalá de Henares, Spain, in June 2016. About 200 professionals and researchers from 18 different countries attended the Congress. This book will be of interest to researchers in the field of architecture and Engineering. Topics discussed are Innovations in Architecture, graphic design and architecture, history and heritage among others.
Preface -- Part I: Innovation Teaching Strategies.- Part II: Design and Education.- Part III. Design and Architecture -- Part IV: History and Cultural Heritage.
Keywords: Engineering design; Buildings -- Design and construction; Construction industry -- Management; Art -- Study and teaching; Engineering Design; Building Construction and Design; Construction Management; Creativity and Arts Education